2013
DOI: 10.1111/epi.12087
|View full text |Cite
|
Sign up to set email alerts
|

Patients' and neurologists' perception of epilepsy and psychogenic nonepileptic seizures

Abstract: Summary Purpose Although differences in illness perceptions between neurologists and patients with epilepsy or psychogenic nonepileptic seizures (PNES) are likely to be clinically relevant, this is the first study to attempt a direct comparison. In addition, this study compares the illness perceptions of patients with epilepsy with those of patients with PNES. Methods Thirty‐four patients with epilepsy, 40 patients with PNES, and 45 neurologists were recruited. All patient participants completed versions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 50 publications
(86 reference statements)
8
44
0
1
Order By: Relevance
“…Teachers' reactions and indirect attitudes would usually be illustrated by snide comments that indicated that they believed that the participants could control the seizures. Advice and simplistic solutions, such 8 as that they should be less stressed, gave a feeling of not being understood. In the workplace, participants felt delegitimized by employers and colleagues stating that it was up to themselves to recover.…”
Section: Delegitimizing Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers' reactions and indirect attitudes would usually be illustrated by snide comments that indicated that they believed that the participants could control the seizures. Advice and simplistic solutions, such 8 as that they should be less stressed, gave a feeling of not being understood. In the workplace, participants felt delegitimized by employers and colleagues stating that it was up to themselves to recover.…”
Section: Delegitimizing Experiencesmentioning
confidence: 99%
“…However, qualitative research on NES is generally lacking [2,3]. While some studies have investigated the experiences of individuals with NES in relation to their interactions with healthcare services [4 -7], and how they understand their condition [3,[8][9][10][11][12][13], we have found only one study that focused particularly on experiences in everyday life [14].…”
Section: Introductionmentioning
confidence: 98%
“…This finding was not present in the ND pairs. This has important practical implications for clinicians who wish to discuss potentially relevant psychological factors with patients with FNSD [2,38]. Our findings suggest that, whilst potentially still requiring persuasion, relatives are more likely to accept that FNSD could be linked to stress, emotional problems or coping difficulties.…”
Section: Discussionmentioning
confidence: 89%
“…Patients with functional weakness and weakness due to ND were recruited prospectively by with those of neurologists [2].…”
Section: Recruitment Of the Weakness Groupsmentioning
confidence: 99%
See 1 more Smart Citation